Profiling the 3D interaction between germ cell tumors and microenvironmental cells at the transcriptome and secretome level. Issue 17 (26th July 2022) - Skowron, Margaretha A.; Eul, Katharina; Stephan, Alexa; Ludwig, Gillian F.; Wakileh, Gamal A.; Bister, Arthur; Söhngen, Christian; Raba, Katharina; Petzsch, Patrick; Poschmann, Gereon; Kuffour, Edmund Osei; Degrandi, Daniel; et al.
Abstract : The tumor microenvironment (TM), consisting of the extracellular matrix (ECM), fibroblasts, endothelial cells, and immune cells, might affect tumor invasiveness and the outcome of standard chemotherapy. This study investigated the cross talk between germ cell tumors (GCT) and surrounding TM cells (macrophages, T‐lymphocytes, endothelial cells, and fibroblasts) at the transcriptome and secretome level. Using high‐throughput approaches of three‐dimensional (3D) co‐cultured cellular aggregates, this study offers newly identified pathways to be studied with regard to sensitivity toward cisplatin‐based chemotherapy or tumor invasiveness as a consequence of the cross talk between tumor cells and TM components. Mass‐spectrometry‐based secretome analyses revealed that TM cells secreted factors involved in ECM organization, cell adhesion, angiogenesis, and regulation of insulin‐like growth factor (IGF) transport. To evaluate direct cell–cell contacts, green fluorescent protein (GFP)‐expressing GCT cells and mCherry‐expressing TM cells were co‐cultured in 3D. Afterward, cell populations were separated by flow cytometry and analyzed by RNA sequencing. Correlating the secretome with transcriptome data indicated molecular processes such as cell adhesion and components of the ECM being enriched in most cell populations. Re‐analyses of secretome data with regard to lysine‐ and proline‐hydroxylated peptides revealed a gain in proteins, such as collagens and fibronectin. Cultivation of GCT cells on collagen I/IV‐ or fibronectin‐coated plates significantly elevated adhesive and migratory capacity, while decreasing cisplatin sensitivity of GCT cells. Correspondingly, cisplatin sensitivity was significantly reduced in GCT cells under the influence of conditioned medium from fibroblasts and endothelial cells. This study sheds light on the cross talk between GCT cells and their circumjacent TM, which results in deposition of the ECM and eventually promotes a pro‐tumorigenic environment through enhanced migratory and adhesive capacity, as well as decreased cisplatin sensitivity. Hence, our observations indicate that targeting the ECM and its cellular components might be a novel therapeutic option in combination with cisplatin‐based chemotherapy for GCT patients. Abstract : This study evaluated the interaction between germ cell tumors and their surrounding microenvironment. As such, the secretome has been analyzed to identify secreted factors, while transcriptome‐wide changes upon direct cell–cell interaction by means of 3D co‐cultures determined the deregulated gene sets. Subsequently, in vitro analyses were performed to validate the findings.